(untitled) (Research, Society and Development, 2020)
In Brazil, along its history, the Technical Professional Education in High School level (TPEHS) has evolved into various proposals and, currently, the technical professional capacitation is amply disseminated as High School Technical Courses. In this educative level some authors believe that the learning divergence and limitations brought from the Elementary School interferes directly on the school success. However, what is observed is that from the beginning of the course, an educational homogeneity among the students is taken for granted, which is not true. Motivated by this, various authors have proposed the use of methodological instruments destined to obtaining information about the students’ learning gap in previous years over the contents assumed as pre-requirements for the course subjects, highlighting among these methodologies the Diagnostic Evaluation (DE). In this paper we present a Systematic Literature Review (SLR) related to the Diagnostic Evaluation in the TPEHS, specifically on the entrant students. Thus, a SLR methodology was developed and is described in this investigation. The results of the SLR final selection are described in a summarized way highlighting the main methodologies and contributions. We concluded that the proposals presented in the papers aim at contributing to reduce the failure rate and evasion from TPEHS and, furthermore, contribute to divulge the theme and open opportunities for further and stronger developments and interventions in the TPEHS.